7T MRI cerebral leptomeningeal enhancement is common in relapsing-remitting multiple sclerosis and is associated with cortical and thalamic lesions - Zurawski, Jonathan; Tauhid, Shahamat; Chu, Renxin; Khalid, Fariha; Healy, Brian C; Weiner, Howard L; Bakshi, Rohit (Multiple sclerosis, 2020)
Background: Meningeal inflammation may contribute to gray matter (GM) involvement in multiple sclerosis (MS) and is proposed to manifest as magnetic resonance imaging (MRI) leptomeningeal enhancement (LME). Objective: To investigate how LME relates to GM lesions in relapsing-remitting multiple sclerosis (RRMS) at 7T. Methods: A total of 30 RRMS subjects (age (mean ± standard deviation (SD)): 44.0 ± 11.3 years, 93% on disease-modifying treatment) and 15 controls underwent gadolinium-enhanced three-dimensional (3D) MP2RAGE (magnetization-prepared 2 rapid gradient-echo) and fluid-attenuated inversion recovery (FLAIR) MRI. LME, cortical lesions (CLs), thalamic lesions (TLs), and white matter (WM) lesions were expert-quantified. Wilcoxon rank-sum, two-sample t-tests, Spearman correlations, and regression models were employed. Results: Two-thirds (20/30) of MS subjects and 1/15 controls (6.7%) had LME. LME+ MS subjects had 2.7 ± 1.5 foci, longer disease duration (14.9 ± 10.4 vs. 8.1 ± 5.7 years, p = 0.028), increased CL number (21.5 ± 12.6 vs. 5.5 ± 5.0, p < 0.001) and volume (0.80 ± 1.13 vs. 0.13 ± 0.13 mL, p = 0.002), and increased TL number (3.95 ± 2.11 vs. 0.70 ± 1.34, p < 0.001) and volume (0.106 ± 0.09 vs. 0.007 ± 0.01 mL, p < 0.001) versus LME– subjects. LME focus number correlated more highly with CL (rs = 0.50, p = 0.01) and TL (rs = 0.81, p < 0.001) than WM lesion (rs = 0.34, p > 0.05) volume. Similar LME–CL number associations were observed in unadjusted and WM lesion–adjusted comparisons (both p < 0.001). Conclusion: Cerebral LME is common in RRMS at 7T and is independently associated with GM injury. We hypothesize that cerebrospinal fluid (CSF)-related inflammation links cortical and thalamic injury.